(3cJGH fgGjI GdGNJUGQs - (3CHh Ydj CMeO Hf YHO GdQMef, GHf efOhjg GdCUagGfj,J (B372 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdMeO dg YfO cd bhd GdebGdI GdChdi ai Ndb GdEfSGf hJQcjH GdLSe s
(3BNQgG (B:s
(3GdHGH GdSGHY efgG ai GdMjGJ GdWHbI hgj Mei GdOb EPG PGH dMe GdeMehe hSbWJ bhJg JeJ GdebGdI GdYGTQI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3jdjg cJGH Ydd GdehJ dSbWG Hf dhbG hdcfg de jUhQ efg ZjQ BNQ UaMI abWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1984s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs